TRANCEDENTAL COMMUNICATION (A SOCIO PHENOMENOLOGY PERSPECTIVE) - Yunitasari, Yunitasari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2009)
Phenomenological Sociology einphazing the subjective of exctsttng g phenomena, which isfrom the seen socialfactthere is something urge individual so to take action for something that he believe. that is right. The phenomena doesnot refer lo the society in general, but refer to individual which sees human as agroup of individual which has different character as- well as has differentperception, attention. also interpretation. For 'example the movement of Al- Qiyadah Al-Islamiyah and Ahmadiyah Al-Qadiyan.